A feedforward control for grid-connected inverter under unbalanced and distorted conditions / Alireza Shayesteh Fard - Alireza, Shayesteh Fard (2016)
Grid-connected inverters utilizing renewable energy sources (e.g., photovoltaic, wind, fuel cell, etc.) are growing rapidly in recent years along with the constantly growing global demand for electricity. The utility is subjected to imbalance and distortion caused by unbalanced and nonlinear loads. Critical and random voltage disturbances could be established by time-varying loads like arc furnaces, the fluctuating output power of the wind and photovoltaic generation, voltage transients caused by line-start induction motors, and voltage transients associated with capacitor switching. These kind of voltage disturbances are stochastic in nature, with durations that differ from a small fraction of a cycle to some cycles. The two-level three-phase three-wire voltage-sourced inverter has become one of the main building blocks of renewable energy systems. In spite of weak grid condition; a grid-connected inverter must inject a synchronously regulated sinusoidal current to the utility grid with required low total harmonic distortion (THD) and high power factor. To overcome these challenges grid-connected inverters should provide unbalanced and distorted voltages. Hence, a new scalar implicit zero-sequence discontinuous pulse width modulation (IZDPWM) technique for three-phase three-wire two-level grid-connected voltage source inverters under the weak grid condition is presented. The proposed technique is the first scalar method that uses line-to-line voltages as reference signals. IZDPWM-based feedforward control strategy is proposed for current regulated grid-connected voltage source inverters under unbalanced and distorted condition. The feedforward control strategy is chosen because it can reject a large number of grid voltage harmonics simultaneously, while providing a clean sinusoidal current waveform to the grid. Regardless the grid topology, the compatible IZDPWM exactly copies the distorting harmonics of the grid voltage. Hence, a sinusoidal current is injected to the grid. IZDPWM-based closed loop controller minimizes low order harmonics in the grid current, and compensate for dc-link voltage ripple, deadtime delays, and semiconductor device voltage drops. For straightforward and significant current control using PI, the three-phase ac current is transferred into the synchronous d–q rotating frame whereas the feedforward compensation of the grid voltage is implemented in abc frame. Appling IZDPWM-based controller; pure sinusoidal current is injected to the grid under balanced, unbalanced, and distorted conditions. Moreover, under weak grid condition in spite of phase voltages, line-to-line voltages are measured by two sensors only. Thus, overall system cost is reduced and reliability of control system is increased. IZDPWM-based feedforward control was extensively tested under balanced, unbalanced, and distorted conditions in both simulation and experimental testes. The compatibility IZDPWM with the line-to-line voltages feedforwarding leads to an adequate control performance with robustness against dynamic voltage disturbances. By applying the proposed IZDPWM-based feedforward control, high quality injected current with low THD (0.888 %) and high power factor (0.999) are obtained.